2014
DOI: 10.1002/ijc.28569
|View full text |Cite
|
Sign up to set email alerts
|

High prevalence ofGPRC5Agermline mutations inBRCA1-mutant breast cancer patients

Abstract: In a search for new breast cancer (BC) predisposing genes, we performed a whole exome sequencing analysis using six patient samples of familial BC and identified a germline inactivating mutation c.183delG [p. Arg61fs] in an orphan G protein-coupled receptor GPRC5A. An extended case-control study revealed a tenfold enrichment for this mutation in BC patients carrying the 5382insC allele of BRCA1, the major founder mutation in the Russian population, compared to wild-type BRCA1 BC cases [6/117 (5.1%) vs. 8/1578 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(30 citation statements)
references
References 43 publications
1
29
0
Order By: Relevance
“…PGM1 is known to be induced under hypoxic conditions and promotes cancer cell survival (35). In addition, it has been shown that GPRC5A is a modifier of breast cancer risk in breast cancer (BRCA)-mutation carriers and GPRC5A inactivation negatively affects BRCA1-mediated DNA repair (36). We found that UHRF1 is involved in the up-regulation of SCD1 and SPRY4 but not of PGM1 and GPRC5A.…”
Section: Discussionmentioning
confidence: 76%
“…PGM1 is known to be induced under hypoxic conditions and promotes cancer cell survival (35). In addition, it has been shown that GPRC5A is a modifier of breast cancer risk in breast cancer (BRCA)-mutation carriers and GPRC5A inactivation negatively affects BRCA1-mediated DNA repair (36). We found that UHRF1 is involved in the up-regulation of SCD1 and SPRY4 but not of PGM1 and GPRC5A.…”
Section: Discussionmentioning
confidence: 76%
“…Therefore, rare germ-line defects may act in a cooperative manner for cancer development. In agreement with this notion, our exome sequencing study led to the identification of rare mutation in a GPRC5A gene, which appears to significantly influence the penetrance of BRCA1 gene [135]. Studies on oligogenic inheritance may require the development of novel bioinformatics tools, which allow for robust analysis of gene combinations.…”
Section: Article In Pressmentioning
confidence: 55%
“…Gracia-Aznarez et al [22] and Kiiski et al [21] revealed rare mutations in the FANCM gene, which turned out to be overrepresented in breast cancer cases vs. controls. Arguably, the study of Sokolenko et al [135] is the most successful for the time being: they reported identification of recurrent mutations in the RECQL gene, which occurred approximately 5 times more frequently in patients vs. healthy donors, and were present in 0.69% patients from Poland and in 0.23% BC cases in Canada. Still, the frequency of RECQL germ-line mutations in affected women is manifold lower as compared to "classical" BC genes.…”
Section: Breast Cancermentioning
confidence: 96%
See 1 more Smart Citation
“…The GPRC5A gene was located on chromosome 12p13-p12.3, and its promoter contained an RA response element to which nuclear retinoid receptors (RAR and RXR) can bind [6]. In recent years, GPRC5A had been receiving increasing attentions as it had been shown to play important roles in human cancers, dysregulation of GPRC5A gene had been associated with several cancers including lung cancer [7], breast cancer [8], and colorectal cancer [9]. In nonsmall cell lung carcinoma, Tao and colleagues [6] reported that the mRNA expression levels of GPRC5A were lower in human lung tumors than in adjacent normal tissues.…”
Section: Introductionmentioning
confidence: 99%